1977
DOI: 10.1115/1.3439223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spring Parameters to Satisfy Specified Energy Levels in Planar Mechanisms

Abstract: The potential energy storage capabilities of linear springs are integrated with the nonlinear motion of mechanisms to provide approximation of desired counter-loading functions. The approximating function is required to be identical to the desired function at a number of precision points. The work is directly analogous to the algebraic form of kinematic synthesis, thus enabling an immediate conceptual grasp by those already familiar with kinematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In this case, the above equations can still be applied but vyitb the term Tm in eqs. (8) and (10) replaced by T v , and the term T m ll in eq. (12)…”
Section: Extension Of the Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the above equations can still be applied but vyitb the term Tm in eqs. (8) and (10) replaced by T v , and the term T m ll in eq. (12)…”
Section: Extension Of the Proposed Methodsmentioning
confidence: 99%
“…Cenova [6] and Skreiner [7] suggested the use of a spring attached to the input and output links respectively, to reduce the fluctuation of the input torque. Mathew and Tesar [8,9] established a method for synthesis of spring parameters to satisfy specified energy levels in planar mechanisms. The method was employed for the minimization of the fluctuation of the input torque.…”
Section: Introductionmentioning
confidence: 99%
“…For simulating the kinematic behavior of a CM, only approximation methods are considered, given that exact solutions only exist for specific shapes whereas a general solution is sought. In literature, two distinctive approaches for the modeling of compliant kinematics are being used extensively: the Finite Element Analysis (FEA) [17,20,37,[39][40][41][42] and Pseudo-Rigid-Body (PRB) models [43][44][45][46][47].…”
Section: Compliance Modelingmentioning
confidence: 99%
“…By taking the energy stored in compliant members into account, desired force, torque and energy characteristics can be specified upfront and designed for. Matthew and Tesar [44] have presented such an extended synthesis method by giving analytical formulations for the synthesis of springs in planar mechanisms in order to provide balancing properties. Roth and Huang [45] presented a method for designing spring elements to match known external forces.…”
Section: Synthesis With Compliance: Kinematics and Dynamicsmentioning
confidence: 99%
“…A number of authors have examined spring-based equilibrators for static mass balancing. The synthesis of such mechanisms has been investigated by Hain (1961) and Matthew and Tesar (1977). More recently, Soper, Mook, and Reinholtz (1997) suggested that spring equilibrators may have application in dynamic systems as a low-cost means of modifying the system potential energy.…”
Section: Introductionmentioning
confidence: 99%